Longer duration entry mitigates nystagmus and vertigo in 7-Tesla MRI - Pogson, Jacob M.; Shemesh, Ari; Roberts, Dale C.; Zee, David S.; Otero-Milan, Jorge; Ward, Bryan K. (Frontiers in Neurology, 2023)
Introduction: Patients and technologists commonly describe vertigo, dizziness, and imbalance near high-field magnets, e.g., 7-Tesla MRI scanners. We sought a simple way to alleviate vertigo and dizziness in high-field MRI scanners by applying the understanding of the mechanisms behind magnetic vestibular stimulation and the innate characteristics of vestibular adaptation. Methods: We first created a 3D control systems model of the direct and indirect vestibulo-ocular reflex (VOR) pathways, including adaptation mechanisms. The goal was to develop a paradigm for human subjects undergoing a 7T MRI scan to optimize the speed and acceleration of entry and exit into the MRI machine to minimize unwanted vertigo. We used this paradigm and recorded 3D binocular eye movements (horizontal, vertical, torsion) and the subjective experience of eight normal individuals within a 7T MRI. The independent variables were the duration of entry and exit from the MRI bore, the time inside the MRI bore, and the magnetic field strength; the dependent variables were nystagmus slow-phase eye velocity (SPV) and the sensation of vertigo. Results: In the model, when the participant was exposed to a linearly increasing magnetic field strength, the per-peak (after entry into the MRI) and post-peak (after exiting the MRI) responses of nystagmus SPV were reduced with increasing duration of entry and exit, respectively. There was a greater effect on the per-peak response. The entry/exit duration and peak response were inversely related, and the nystagmus was decreased the most with the five-minute duration paradigm (the longest duration modeled). The experimental nystagmus pattern of the eight normal participants matched the model, with increasing entry duration having the strongest effect on the per-peak response of nystagmus SPV. Likewise, all participants described less vertigo with the longer duration entries. Conclusion: Increasing the entry duration into and out of a 7T MRI reduced or eliminated vertigo symptoms and reduced nystagmus peak SPV. Model simulations suggest that central processes of vestibular adaptation account for these effects. Two-minute entry and 20-second exit durations are a practical solution to mitigate vertigo and other discomforting symptoms associated with 7T MRIs. In principle, these findings also apply to different magnet strengths.